2010
DOI: 10.1099/mic.0.033126-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in adherence and virulence gene expression between two outbreak strains of enterohaemorrhagic Escherichia coli O157 : H7

Abstract: The Escherichia coli O157 : H7 TW14359 strain was implicated in a multi-state outbreak in North America in 2006, which resulted in high rates of severe disease. Similarly, the O157 : H7 RIMD0509952 (Sakai) strain caused the largest O157 : H7 outbreak to date. Both strains were shown to represent divergent phylogenetic lineages. Here we compared global gene expression patterns before and after epithelial cell exposure, as well as the ability to adhere to and invade epithelial cells, between the two outbreak str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 75 publications
(72 reference statements)
5
51
1
Order By: Relevance
“…Adhesion genes iha and saa and the genes coding enzymes that assist in the colonization of STEC espP, katP, and stcE were sporadically possessed. However, the prevalence of these genes was not correlated with the level of symptom and the cell-adhesion activity Table 1 . On the other hand, it has been reported that there is variation in the expression of the genes on LEE among STEC O157 strains with differing cell-adhesion activity Abu-Ali et al, 2010Tobe et al, 2005 . Accordingly, we next analyzed the expression of these genes eae, espB, espD, and tir among six strains ESC531, ESC574, ESC552, ESC553, ESC554, ESC569 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion genes iha and saa and the genes coding enzymes that assist in the colonization of STEC espP, katP, and stcE were sporadically possessed. However, the prevalence of these genes was not correlated with the level of symptom and the cell-adhesion activity Table 1 . On the other hand, it has been reported that there is variation in the expression of the genes on LEE among STEC O157 strains with differing cell-adhesion activity Abu-Ali et al, 2010Tobe et al, 2005 . Accordingly, we next analyzed the expression of these genes eae, espB, espD, and tir among six strains ESC531, ESC574, ESC552, ESC553, ESC554, ESC569 .…”
mentioning
confidence: 99%
“…First, we examined the variations in adhesion activity to Caco-2 cells among the strains. Abu-Ali et al Abu-Ali et al, 2010 showed differences in the level of adhesion to epithelial duplicate for every sample. The amplifications of eae and 16S rRNA gene were performed with the primers previously described Bergholz et al, 2007 Nielsen andAndersen, 2003 .…”
mentioning
confidence: 99%
“…It has been reported that cattle are main reservoir for STEC (2,20,26). Investigations carried out in different part of Europe, Asia, North America have showed that 10-80% cattle were infected with STEC (1,2,5,8,27,39). The occurrence of E.coli O157:H7 were also detected in different regions of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of STEC O157:H7 is associated with a number of virulence factors, including Shiga toxins 1 and 2, as well as intimin and enterohaemolysin (1,2,6,8,27,31,37). Kang et al (19) reported that stx(1) and stx(2) appear to play a major role in the pathogenesis of haemorrhagic colitis and haemolyticuremic syndrome and STEC strains predominantly carries either stx(1) or stx(2) or both genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation